Biomechanical optimization of a custom-made positioning and fixing bone plate for Le Fort I osteotomy by finite element analysis. (1st January 2016) - Huang, Shao-Fu; Lo, Lun-Jou; Lin, Chun-Li
Abstract: This study integrates image-processing, finite element (FE) analysis, optimization and CAM techniques to develop a bone plate that can provide precise positioning and fixation for the Le Fort I osteotomy. Two FE 3D models using commercial mini-plate and continuous bone plates were generated by integrating computed tomography images and CAD system for simulations under the worst load condition. The goal driven optimization method was used to examine the system performance using certain minimum output values for relative micro-movement between the two maxillary bone segments and stress for the bone plate to seek maximum reduction volume in a continuous plate. The simulation results indicated that the maximum stress/relative micro-movement was 1269.20 MPa/133.66 μm and 418.37 MPa/92.37 μm for the commercial straight mini-plate and continuous fixation types, respectively. The optimal design plate found the volume reduction rate reach 24.3% compared to the continuous bone plate and the decreased variations in stress/relative micro-movement were 65.14% (442.36 MPa) and 29.36% (96.53 μm) when compared to values obtained from the commercial mini-plate plate. The optimal bone plate can be manufactured using a 5-axes milling machine and fixed onto the freed separate maxillary segments of a rapid prototyping model to provide precise positioning/fixation and present adequate strength/stability in the Le Fort I osteotomy.